A behavioral approach to institutional economics rules of the game and cooperation behavior - Arslanoğlu, Selin (İstanbul Bilgi Üniversitesi, 2019)
In the behavioral economics literature, the dynamics of cooperation in groups have received a great deal of interest. There are many studies investigating the effect of some individual characteristics and external factors on cooperation behavior of individuals in different settings. The findings of those studies show that the effect of a policy on cooperation is greater when the policy is chosen democratically by group members than when it is imposed exogenously. With this motivation, in this thesis study, I mainly focus on whether cooperation behavior of individuals is influenced by the mechanisms imposing the rules when there is a conflict between what is individually optimal and what is optimal for the society as a whole. In an experimental setting, using a prisoners’ dilemma game which can be transformed into a coordination game, the study questions if people can coordination the socially efficient equilibrium when the transformation is imposed democratically. Also, with a coordination game it is investigated how people coordinate when there are more than one equilibrium. The results cannot confirm the claim that democratic decision-making processes increase cooperation but suggest that individual-level cooperation is influenced by prior mutual cooperation experience and some personal characteristics.

Gruplardaki iş birlikçi davranış dinamikleri, davranışsal iktisat literatüründe pek çok akademik çalışmaya konu olmuştur. Literatürde bulunan çalışmaların büyük çoğunluğu, farklı koşullar altında, dışsal faktörlerin ve bireylerin kişisel tercihlerinin işbirlikçi davranışın asıl etkilediği sorusuna cevap aramaktadır. Bu çalışmalardan elde edilen bulgular ve sonuçlar, kuralların demokratik yöntemlerle koyulması durumunda, bireylerin koyulan kurallara uyma eğilimi sergileyip daha iş birlikçi davrandıklarını göstermiştir. Literatürdeki bu sonuçlardan hareketle, bu tez çalışmasında mahkumlar ikilemi oyunu kullanılarak, toplumsal ve bireysel tercihlerin çatıştığı durumlarda iş birlikçi davranışla kural koyma yöntemleri arasındaki ilişkinin nasıl şekillendiği üzerinde durulmaktadır. Ayrıca, bir koordinasyon oyunuyla bireylerin iki farklı denge olması durumunda nasıl koordine oldukları da incelenmektedir. Çalışma kapsamında yapılan iktisadi deneylerde, demokratik karar verme süreçlerinin işbirlikçi davranışı olumlu etkilediğini destekleyen sonuçlara ulaşılamamıştır. Ancak, deneylerden elde edilen sonuçlar bireysel işbirliği davranışının bireylerin daha önceki karşılıklı iş birliği deneyimlerinden ve bazı kişisel özelliklerden etkilendiği ortaya koymuştur.
Kurumsal iktisata davranışsal bir yaklaşım: Oyunun kuralları ve işbirlikçi davranış